Development of Hospital Enteral Formula for Diabetes Using Tempeh Flour with Dragon Fruit and Tomato Addition - Wijayanti, Dian; Saraswati, Indah Wening; Khairunnisa, Anggita Nadya (International Journal of Health and Information System, 2024)
This study aimed to develop a novel enteral formula for diabetes patients using tempeh flour with dragon fruit and tomato additions. An experimental design was employed to formulate and evaluate the nutritional content, viscosity, and organoleptic properties of the developed formula. Results showed that the formula had a high energy content of 926.1 kcal/100ml, with 41.6g/100ml of protein, 26.8g/100ml of fat, and 131.4g/100ml of carbohydrates. Viscosity testing indicated appropriate flow properties for enteral feeding, with 7ml of 10ml flowing in 10 seconds. However, organoleptic evaluation by seven panelists revealed low acceptance scores on a 4-point scale: color (mean 1.71), aroma (1.43), taste (1.43), and texture (2.29). While the formula demonstrates potential in terms of nutritional content and viscosity, significant improvements are needed to enhance its sensory acceptability. This research contributes to the development of plant-based enteral formulas for diabetes management, highlighting the challenges in balancing nutritional requirements with organoleptic qualities. The high carbohydrate content, while potentially beneficial for energy provision, raises concerns about glycemic control in diabetic patients. Further optimization of the formula's composition and clinical trials are recommended to assess its efficacy in diabetes care and to address the sensory and nutritional challenges identified in this study.